Locally preserved α → β phase transition in natural radiation-damaged titanite (CaTiSiO5): evidence from laser-induced photoluminescence and dielectric measurements. (21st December 2017) - Beirau, Tobias; Murawski, Dawid; Behrens, Harald; Salje, Ekhard K H; Groat, Lee A; Kaden, Ronny; Pöllmann, Herbert; Bismayer, Ulrich
Abstract: In situ temperature-dependent laser-induced photoluminescence and dielectric measurements provide new evidence for the local occurrence of the α → β phase transition near 500 K in the preserved crystalline parts of natural radiation-damaged titanite (sample E2335 with 24% amorphous fraction, containing Fe and Al impurities). Photoluminescence spectroscopic measurements show an anomaly in the vicinity of 500 K. The temperature-dependent evolution of the real part of the electrical conductivity ( σ ) and the real ( ε ′) and the imaginary ( ε ″) part of the complex dielectric permittivity ( ε * ) of titanite have been measured at various AC frequencies ( 1.2–96.8 kHz). Despite the masking and smearing effect of impurities and defects, the temperature-dependent behaviour of ε ′ and ε ″ around the transition temperature of the investigated natural titanite E2335 shows a remarkable similarity to that of the synthetic end-member material (see Zhang et al (1995 Phys. Chem. Miner .22 41–9)). This study indicates the suitability of photoluminescence and impedance spectroscopy for the detection of phase transitions, even in heavily disordered systems.